PENERAPAN GOOD CORPORATE GOVERNANCE (GCG) DAN PENGARUHNYA TERHADAP KINERJA PERUSAHAAN - Budidarma, I Gusti Agung Musa (JBE (Journal of Business and Economics); Volume 12 No.1, 2013 JBE UNKLAB, 2013)
This study seeks to find out whether the GCG implementation is affecting the firm’s performance. The sample of this study are the firms participating in CGPI research and rating. Independent variables in this study are independent commissioner, audit committee, and CGPI. While dependent variables consist of ROA, DTA, and PER.  The simple regression analysis is used to answer the hypothesis.  The findings indicate that partially independent commissioner has significant influence toward ROA and DTA but not for PER. While, audit committee has no significant influence toward ROA, DTA, and PER. In addition, CGPI has affected significantly to DTA and PER.